Options for Endocrine-Refractory, Hormone Receptor–Positive Breast Cancer: Which Target and When?. Issue 35 (10th December 2021) - Borges, Virginia F.
Abstract : The Oncology Grand Rounds series is designed to place original reports published in the Journal into clinical context. A case presentation is followed by a description of diagnostic and management challenges, a review of the relevant literature, and a summary of the authors' suggested management approaches. The goal of this series is to help readers better understand how to apply the results of key studies, including those published in Journal of Clinical Oncology, to patients seen in their own clinical practice . Abstract :